Liquid crystal precursor system as a vehicle for curcumin‐mediated photodynamic inactivation of oral biofilms. Issue 2 (13th October 2022) - Reina, Bárbara Donadon; Santezi, Carolina; Malheiros, Samuel Santana; Calixto, Giovana; Rodero, Camila; Victorelli, Francesca Damiani; Chorilli, Marlus; Dovigo, Lívia Nordi
Abstract: Curcumin has great potential as a photosensitizer, but it has low solubility in aqueous solutions. This study reports the antimicrobial efficacy of photodynamic inactivation (PDI) mediated by a curcumin‐loaded liquid crystal precursor (LCP) on in situ dental biofilms. Thirty volunteers used intraoral devices containing enamel samples for 48 hours for biofilm formation. The samples were then removed from the device and treated either with LCP with 160 μM of curcumin plus illumination at 18 J/cm 2 (C + L+ group) or with LCP without curcumin in the dark (C – L − group). Following this, the biofilm from the samples was plated for quantifying the viable colonies at 37°C for 48 hours. Specific and nonspecific media were used for the presumptive isolation of Streptococcus mutans, Lactobacillus species/aciduric microorganisms, Candida species, and total microbiota. The C + L+ group showed a highly significant ( P  < .001) reduction in the log10 (colony forming units/mL) values as compared to the C − L − group for all culture media. Hierarchical linear regression indicated that there may be predictors at individual volunteer level explaining the difference in the PDI efficacy among different individuals ( P  = .001). The LCP system retained curcumin and released it slowly and continuously, thus protecting the drug from photodegradation. LCP with curcumin is considered effective for the photoinactivation of dental biofilms, but the PDI efficacy may differ based on the host's individual characteristics. Abstract : Curcumin has great potential as a photosensitizer, but it has low solubility in aqueous solutions. This study reports the antimicrobial efficacy of photodynamic inactivation (PDI) mediated by a curcumin‐loaded liquid crystal precursor (LCP) on in situ dental biofilms. The LCP system retained curcumin and released it slowly and continuously, thus protecting the drug from photodegradation. LCP with curcumin is considered effective for the photoinactivation of dental biofilms, but the PDI efficacy may differ based on the host's individual characteristics.